PsycEXTRA Dataset 2013
DOI: 10.1037/e623272013-001
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Changes in Drinking: Relationship to Treatment Outcomes

Abstract: Pretreatment changes in alcohol use challenges the assumption that the major portion of the change process occurs after treatment entry. Greater understanding of the behavior change process prior to treatment has the potential to improve our understanding of behavioral changes during treatment. In this study, participants (N = 45) were recruited for a clinical trial examining multiple mechanisms of change in cognitive-behavioral treatment for alcohol dependence. Using data from both baseline and end of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 9 publications
4
24
1
Order By: Relevance
“…In the general psychotherapy literature, studies of pretreatment change have shown that symptom change consistently occurs after the initial phone call when an appointment is scheduled, before the first treatment session (Kindsvatter et al, ; Lawson, ; Ness and Murphy, ; Weiner‐Davis et al, ; West et al, ). In the substance abuse literature, a similar pattern has been observed in studies that report reductions in or cessation of use that occurs between the initial phone call and the first clinical research assessment (Epstein et al, ; Kaminer et al, ; Morgenstern et al, ; Ondersma et al, ; Penberthy et al, ; Sobell, ; Stasiewicz et al, ).…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…In the general psychotherapy literature, studies of pretreatment change have shown that symptom change consistently occurs after the initial phone call when an appointment is scheduled, before the first treatment session (Kindsvatter et al, ; Lawson, ; Ness and Murphy, ; Weiner‐Davis et al, ; West et al, ). In the substance abuse literature, a similar pattern has been observed in studies that report reductions in or cessation of use that occurs between the initial phone call and the first clinical research assessment (Epstein et al, ; Kaminer et al, ; Morgenstern et al, ; Ondersma et al, ; Penberthy et al, ; Sobell, ; Stasiewicz et al, ).…”
mentioning
confidence: 57%
“…Several of these studies found changes in alcohol use after the initial phone call (when screening information is obtained), but before the baseline assessment (Epstein et al, ; Sobell, ; Stasiewicz et al, ). In 2 studies, greater pretreatment reductions in the quantity and frequency of alcohol use predicted better 3‐month (Stasiewicz et al, ) and 12‐month drinking outcomes (Epstein et al, ). Thus, it appears that significant change in drinking may occur after the decision to seek treatment but before the first treatment session, and that these changes often are maintained during and following a course of treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Greater understanding of when avoidance inclinations shift and their subsequent influence on changes in drinking and treatment seeking behaviors may help elucidate processes by which people successfully overcome problematic alcohol use. Of particular interest are changes during pretreatment intervals, as they may predict decreases in drinking often observed prior to the first treatment session (e.g., Stasiewicz et al, in press; Epstein et al, 2005). Finally, future research identifying techniques that enhance or maintain avoidance inclinations may improve treatment outcomes by allowing individuals to successfully cope with acute rises in approach inclinations over the course of treatment.…”
Section: Discussionmentioning
confidence: 99%